Modulation of the input–output function by GABA(A) receptor-mediated currents in rat oculomotor nucleus motoneurons - Torres-Torrelo, Julio (J Physiol, 2014)
The neuronal input–output function depends on recruitment threshold and gain of the firing frequency–current (f–I) relationship. These two parameters are positively correlated in ocular motoneurons (MNs) recorded in alert preparation and inhibitory inputs could contribute to this correlation. Phasic inhibition mediated by γ-amino butyric acid (GABA) occurs when a high concentration of GABA at the synaptic cleft activates postsynaptic GABA(A) receptors, allowing neuronal information transfer. In some neuronal populations, low concentrations of GABA activate non-synaptic GABA(A) receptors and generate a tonic inhibition, which modulates cell excitability. This study determined how ambient GABA concentrations modulate the input–output relationship of rat oculomotor nucleus MNs. Superfusion of brain slices with GABA (100 μm) produced a GABA(A) receptor-mediated current that reduced the input resistance, increased the recruitment threshold and shifted the f–I relationship rightward without any change in gain. These modifications did not depend on MN size. In absence of exogenous GABA, gabazine (20 μm; antagonist of GABA(A) receptors) abolished spontaneous inhibitory postsynaptic currents and revealed a tonic current in MNs. Gabazine increased input resistance and decreased recruitment threshold mainly in larger MNs. The f–I relationship shifted to the left, without any change in gain. Gabazine effects were chiefly due to MN tonic inhibition because tonic current amplitude was five-fold greater than phasic. This study demonstrates a tonic inhibition in ocular MNs that modulates cell excitability depending on cell size. We suggest that GABA(A) tonic inhibition acting concurrently with glutamate receptors activation could reproduce the positive covariation between threshold and gain reported in alert preparation.